Overcoming workplace loneliness : cultivating belonging for a remote workforce - Cenkci, Ada T.; Downing, Megan S.; Bircan, Tuba; Perham-Lippman, Karen (Emerald Publishing Limited, 2023)
Humans are fundamentally social beings who crave belonging, mission, and meaning, especially at work. Drawing on the increasing prevalence of remote work in the post-pandemic era, this book asks how organizations can overcome workplace loneliness and create a sense of belonging. Prioritizing the need to create authentic workplaces to promote inclusion and empower employees to feel comfortable being themselves, chapters present strategies for addressing workplace loneliness based on interviews with remote employees and an examination of successful organizational practices. How, contributors ask, have remote employees experienced workplace loneliness in their organization? What is the role of belonging in tackling this? How can leaders and HR practitioners foster this belonging among remote employees? How does social identity affect employees' abilities to connect within their organization? Rooted in real-world research and insights, Overcoming Workplace Loneliness envisions a world of work where all employees feel valued for their authentic selves and are able to experience the encouragement and comradery of office connection from the comfort of their homes. This pioneering book not only sheds light on workplace loneliness of remote employees, but also provides an in-depth literature review of workplace loneliness to inspire future research.
Includes index.
Keywords: Loneliness in the workplace.; Business & Economics -- Human Resources & Personnel Management.; Office & workplace.; elektronické knihy; electronic books